A Novel Assisted Oocyte Activation Method Improves Fertilization in Patients With Recurrent Fertilization Failure - Wang, Meng; Zhu, Lixia; Liu, Chang; He, Hui; Wang, Cheng; Xing, Chenxi; Liu, Jinming; Yang, Liu; Xi, Qingsong; Li, Zhou; Jin, Lei (Frontiers in Cell and Developmental Biology, 2021)
Total fertilization failure (TFF) occurs in 1-3% of total intracytoplasmic sperm injection (ICSI) cycles and can reoccur in subsequent cycles. Despite the high success rate with the application of assisted oocyte activation (AOA), there are still a small number of couples who cannot obtain fertilized eggs after conventional calcium (Ca2+) ionophores-based ICSI-AOA. Six couples experiencing repeated TFF or low fertilization (＜10%) after ICSI and conventional ICSI-AOA were enrolled in this study. Compared with the regular ICSI group and the conventional ICSI-AOA group, the new AOA method, a combination of cycloheximide (CHX) and ionomycin, can significantly increase the fertilization rate from less than 10% up to approximately 50% in most cases. The normal distribution of sperm-related oocyte activation factor phospholipase C zeta (PLCζ1) in the sperms of the cases indicated the absence of aberrant Ca2+ signaling activation. The results of the whole-embryo aneuploidies analysis indicated that oocytes receiving the novel AOA treatment had the potential to develop into blastocysts with normal karyotypes. Our data demonstrated CHX combined with ionomycin was able to effectively improve the fertilization rate in the majority of patients suffering from TFF. This novel AOA method had a potential therapeutic effect on those couples experiencing TFF, even after conventional AOA, which may surmount the severe fertilization deficiencies in patients with repeated low fertilization or TFF.